Rapid detection of goose hemorrhagic polyomavirus using TaqMan quantitative real-time PCR. (June 2018) - Wan, Chunhe; Cheng, Longfei; Fu, Guanghua; Chen, Cuiteng; Liu, Rongchang; Shi, Shaohua; Chen, Hongmei; Fu, Qiuling; Huang, Yu
Abstract: Due to low doses of infection, an efficient and sensitive virus detection method is necessary to detect low amounts of goose hemorrhagic polyomavirus (GHPV). In this study, we have developed a TaqMan real-time PCR (qPCR) specific assay for the detection of GHPV. Specificity assay showed no cross-reactions with other common waterfowl viruses. The standard curve had a linear correlation of 0.997 and efficiency of 99% between the cycle threshold value and the logarithm of the plasmids copy number. The possible lowest detectable concentration was 35.4 copies/μl; 100 times more sensitive than conventional PCR (detection limit, 3.54 × 10 3 copies/μl). Domestic Jinyun Sheldrakes ducks and their embryonated eggs were found positive of GHPV infection which provides evidence of possible vertical transmission of GHPV. Highlights: A TaqMan real-time PCR method for goose hemorrhagic polyomavirus (GHPV) was developed. The method showed high sensitivity, specificity and reproducibility. Domestic Sheldrakes can be infected in GHPV, which indicates GHPV persistent infection in ducks, China.